1997
DOI: 10.1074/jbc.272.22.14477
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of the Antifibrinolytic Activity of Plasma Carboxypeptidase B

Abstract: The precursor of plasma carboxypeptidase B (pCPB) also known as thrombin-activable fibrinolysis inhibitor can be converted by thrombin to an active enzyme capable of eliminating C-terminal Lys-and Arg-residues from proteins. The activation is about 1000-fold more efficient in the presence of thrombomodulin (TM). We investigated the antifibrinolytic potency of maximally activated pCPB in plasma and explored the antifibrinolytic mechanism of pCPB. During clotting of plasma in the presence of 3.3 NIH units/ml thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
174
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(184 citation statements)
references
References 34 publications
4
174
0
6
Order By: Relevance
“…We, however, recently demonstrated that FDPs produced in a perfused, cross-linked clot vary in molecular weight from 250 (the mass of DD/E) to 10,000 kDa, with the majority of the mass contained in fragments larger than DD/E (9). This suggests that FDPs much larger than DD/E are released into circulation during fibrinolysis, and indeed FDP complexes of at least 2.0 ϫ 10 6 Da have been observed in the plasma of patients with disseminated intravascular coagulation (13,14) and chronic subdural hematoma (15). Whereas a large difference in activity between t-PA and DSPA␣1 would be expected with DD/E, this difference disappears with larger FDPs.…”
Section: Comparison Of Cofactor Activities Of Fdps and Fibrin-mentioning
confidence: 80%
“…We, however, recently demonstrated that FDPs produced in a perfused, cross-linked clot vary in molecular weight from 250 (the mass of DD/E) to 10,000 kDa, with the majority of the mass contained in fragments larger than DD/E (9). This suggests that FDPs much larger than DD/E are released into circulation during fibrinolysis, and indeed FDP complexes of at least 2.0 ϫ 10 6 Da have been observed in the plasma of patients with disseminated intravascular coagulation (13,14) and chronic subdural hematoma (15). Whereas a large difference in activity between t-PA and DSPA␣1 would be expected with DD/E, this difference disappears with larger FDPs.…”
Section: Comparison Of Cofactor Activities Of Fdps and Fibrin-mentioning
confidence: 80%
“…10,11 The shortening of the lysis time caused by PTI is a measure of the antifibrinolytic activity of TAFIa and is expressed as PTI sensitivity ratio (hereafter referred to as PTI ratio), i.e., the ratio between lysis time in the absence of PTI and lysis time in the presence of PTI.…”
Section: Patientsmentioning
confidence: 99%
“…To that purpose, each plasma dilution was incubated for 5 minutes with thrombin (3 U/mL), solulin (1 g/mL), and CaCl 2 (20 mmol/L) to convert all TAFI to TAFIa. 10 Afterwards, the samples were processed as reported above for the determination of PTI-sensitive Cp activity. The amount of TAFIa generated during the clot lysis experiments is expressed as percentage of total TAFI present in normal plasma.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations